1972
DOI: 10.1113/jphysiol.1972.sp009700
|View full text |Cite
|
Sign up to set email alerts
|

A reflex increase in heart rate from distension of the junction between the superior vena cava and the right atrium

Abstract: SUMMARY1. Localized distension of the junction between the superior vena cava and the right atrium without obstructing venous return caused an increase in heart rate.2. This increase in heart rate was a reflex response; the afferent path was in the vagi and the efferent solely in the sympathetic nerves.3. The receptors most likely to be stimulated by the distension of the junction between the superior vena cava and the right atrium are the right atrial receptors located on the endocardial surface of the intrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

1973
1973
2000
2000

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 29 publications
3
32
0
Order By: Relevance
“…Such a response is similar to that elicited by stretching of the vein-atrium juctions in dog and rat (Kappagoda et al 1972;Karim et al 1972;Kaufman et al 1981;Linden, 1988). How injection of DLH at specific locations elicited this pattern is worth considering.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Such a response is similar to that elicited by stretching of the vein-atrium juctions in dog and rat (Kappagoda et al 1972;Karim et al 1972;Kaufman et al 1981;Linden, 1988). How injection of DLH at specific locations elicited this pattern is worth considering.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore increased cardiac output and splanchnic vasoconstriction would be important in maintaining arterial blood pressure following a loss of blood volume. Several studies have shown that there is a reflex reduction in RSNA during acute volume expansion in the rat (Dibona & Sawin, 1985;Haselton et al 1994), the rabbit (Clement et al 1972), the cat (Schad & Seller, 1976) and the dog (Kappagoda et al 1972;Karim et al 1972;Morita & Vatner, 1985). Furthermore, it has been shown in the rat that the initial cardiovascular response to acute volume load is an increase in renal blood flow and an increase in renal vascular conductance (Lovick et al 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As with stroke volume, the greatest increase in heart rate per unit change in mean left atrial pressure occurred when the initial mean left atrial pressure was low, and the increment progressively decreased as the left atrial pressure was elevated further. The heart rate response is presumably due to stretch of cardiopulmonary mechanoreceptors with afferents in the vagus nerve (Ledsome & Linden, 1964;Kappagoda, Linden & Snow, 1972). The greater stretch of these receptors, per unit increase in filling pressure, when the ventricle is small may result in substantial increases in firing rate, but with further filling proportionately less increment in stretch occurs, and the increment in the firing rate per unit pressure change is less (Kuffler, 1954).…”
Section: Discussionmentioning
confidence: 99%
“…In ten dogs the superior vena caval-right atrial junction was stretched without causing changes in the venous return to the heart (Kappagoda, Linden & Snow, 1972a). In nine dogs the right atrium was distended without causing changes in mean right atrial pressure by injecting warm saline (10-16 ml.)…”
Section: Pmentioning
confidence: 99%